The Hemodynamic Stability of Dexmedetomidine during Laparoscopic Uterine Fibroids Surgery: A Randomized Controlled Study - Xia Cao; Xu Ding; Huihui Sun; Lihong Zhang; Xiang Li (IMR Press, 2024)
Background: The aim of this study was to determine whether dexmedetomidine can reduce the circulatory response in laparoscopic uterine fibroids (UF) surgery. Our purpose was to investigate the effect of dexmedetomidine on the circulatory response in laparoscopic UF surgery. Methods: This was a randomized controlled study of 214 patients age range of 40-60 years, American Society of Anesthesiologists (ASA) 1-2 grade, undergoing elective laparoscopic UF surgery at Fuxing Hospital, Capital Medical University from January 2020 to October 2023. Patients were randomly allocated to the non-dexmedetomidine group (Group1) and dexmedetomidine group (Group2). The mean arterial pressure (MAP) and heart rate (HR) were measured: when entering the operation room (MAP1, HR1), immediately at the time of local pituitrin injection (MAP2, HR2), and at 5 minutes after injection of pituitrin (MAP3, HR3). The medications and dosages (propofol, urapidil hydrochloride, fluid) used during the operation were recorded as well as the recovery (drowsiness, chills, nausea, vomiting, dysphoria) after the operation. Total mean time from the beginning of the operation to pituitrin injection (Time1) and recovery time after peaking blood pressure with pituitrin injection (Time2) were also recorded. Results: There were no significant differences in age, height, weight, size and number of UFs, and the location of uterine fibroids between the two groups. There were no differences between the groups for MAP1, MAP2, HR1, HR2, HR3, and Time1 (all p > 0.05), but the dexmedetomidine group was smaller in MAP3 (p = 0.041) and Time2 (p = 0.000) than the non-dexmedetomidine group. There were significant differences in MAP3-MAP1 (p = 0.025), propofol (p = 0.011), and urapidil hydrochloride (p = 0.000) between the two groups. The dexmedetomidine group was smaller in chills (p = 0.002), nausea (p = 0.000), vomiting (p = 0.04), and dysphoria (p = 0.024) than the non-dexmedetomidine group. Conclusions: Dexmedetomidine maintains a stable hemodynamic response and is beneficial to postoperative recovery in laparoscopic UF surgery. Clinical Trial Registration: The study has been registered on https://classic.clinicaltrials.gov/ (registration number: NCT03524950).